Isolation And Identification of Bacteria In The Composting Process of Red Algae (Glacilaria sp) With The Addition of Cow Manure And Waste Household - Muhammad Ridwan Harahap; Husnawati Yahya; Syafrina Sari Lubis; Sugiati Sugiati (Elkawnie, 2021)
Abstract: Bacterial isolation research has been conducted from composting Glacilaria sp with the addition of cow dung and household waste. Glacilaria sp samples were taken from Gampoeng Neheun Pond, Mesjid Raya district, Aceh Besar. The process of composting Glacilaria sp with the addition of other materials is done with a ratio of 2:1, the composting time lasts for 20 days. Leachate sampling is carried out on days 0; 4; 8; 12; 16; and 20 as much as 10 ml. PH, color and smell measurements of the sample are performed on each leachate sampling. The observations obtained 39 Gram-negative isolates and 40 Gram-positive isolates. With morphological forms of cells namely Coccus, Bacill, Diplococcus, Streptoccus, Streptobacillus and Staphylococcus. The bacteria are most commonly found in composting household waste.Abstrak: Telah dilakukan penelitian isolasi bakteri dari pengomposan Glacilaria sp, dengan penambahan kotoran sapi dan limbah rumah tangga. Sampel Glacilaria sp berasal dari tambak Gampoeng Neheun, Kecamatan Masjid Raya Aceh Besar. Proses pengomposan Glacilaria sp dengan penambahan bahan lain dilakukan dengan perbandingan 2:1, waktu pengomposan berlangsung selama 20 hari. Pengambilan sampel lindi dilakukan pada hari ke 0, 4, 8, 12, 16, dan 20 sebanyak 10 ml. Dilakukan pengukuran pH, warna dan bau sampel pada setiap pengambilan sampel lindi. Hasil pengamatan diperoleh 39 isolat Gram negatif dan 40 isolat Gram positif. Dengan bentuk morfologi sel yaitu Coccus, Bacill, Diplococcus, Streptoccus, Streptobacillus dan Staphylococcus. Bakteri yang paling banyak ditemukan pada pengomposan limbah rumah tangga